2016
DOI: 10.1159/000449451
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nutritional Parameters with Clinical Outcomes in Patients with Acute Myeloid Leukemia Undergoing Haematopoietic Stem Cell Transplantation

Abstract: Introduction: In acute myeloid leukemia (AML) patients undergoing allogeneic haematopoietic stem cell transplantation (HSCT), there is uncertainty about the extent of influence nutritional parameters have on clinical outcomes. In this study, we investigated the association between initial body mass index (BMI) and weight loss during HSCT on clinical outcomes in a well-characterised cohort of AML patients. Methods: We analysed data of the Basel stem-cell transplantation registry (‘KMT Kohorte') including all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 30 publications
0
26
0
1
Order By: Relevance
“…72 Our own retrospective study did as well show a correlation of high weight loss during the index hospitalization and increased morbidity and length of hospital stay. 73 However, we also found an association of low pretransplantation body weight with mortality. 73 The result is supported by Xue et al 74 documenting lower survival in underweight patients before transplantation in another retrospective analysis.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…72 Our own retrospective study did as well show a correlation of high weight loss during the index hospitalization and increased morbidity and length of hospital stay. 73 However, we also found an association of low pretransplantation body weight with mortality. 73 The result is supported by Xue et al 74 documenting lower survival in underweight patients before transplantation in another retrospective analysis.…”
Section: Discussionmentioning
confidence: 46%
“…73 However, we also found an association of low pretransplantation body weight with mortality. 73 The result is supported by Xue et al 74 documenting lower survival in underweight patients before transplantation in another retrospective analysis. Dietrich et al 75 examined the association of BMI before the beginning of induction chemotherapy and BMI before transplantation with survival.…”
Section: Discussionmentioning
confidence: 46%
“…Currently, there is no consensus regarding which parameter best determines malnutrition in children undergoing allo-HSCT. Body weight and BMI are easily applicable in clinical practice, but lack information on body composition and are heavily influenced by hydro-electrolytic imbalance occurring during the procedure, thus not directly reflecting the patient's nutritional status [5,6,36,37]. Additional studies comparing laboratory parameters, such as retinol-binding protein, or more detailed anthropometric measures, for example triceps skin fold thickness, are needed to better understand the influence of the type of nutritional support on overall patient nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to improve nutrition in underweight patients before or during transplantation have been proposed. Baumgartner et al [6] compared 90 adult AML patients who underwent myeloablative transplants and received PN with patients who did not receive nutritional therapy and showed that the patients who received PN had higher mortality, more infectious complications, and a greater risk of GVHD.…”
Section: Discussionmentioning
confidence: 99%